Water quality as a predictor of gastrointestinal illness following incidental contact water recreation. (15th October 2015) - Dorevitch, Samuel; DeFlorio-Barker, Stephanie; Jones, Rachael M.; Liu, Li
Abstract: Microbial measures of water quality are predictors of gastrointestinal illness among swimmers in some settings but not in others. Little is known whether water quality measures predict illness among people who engage in popular water recreation activities such as paddling, rowing, fishing, or boating ("incidental contact water recreation"). We sought to evaluate indicator microbes, protozoan pathogens, and turbidity as predictors of gastrointestinal illness following incidental contact water recreation. A cohort study of incidental contact water recreation was conducted in the Chicago, USA area. Recreation took place on inland lakes, rivers, Lake Michigan, and an urban waterway heavily impacted by wastewater effluent. Water samples were analyzed for Escherichia coli, enterococci, somatic coliphages, F+ coliphages, Giardia spp. and Cryptosporidium spp. (oo)cysts, and for turbidity. Median enterococci concentrations were 71.0 and 199.8 colony forming units/100 mL at general use and effluent-dominated waters, respectively. Among 4694 study participants with complete covariate data, 193 (4.1%) developed gastrointestinal illness within three days of water recreation. In multivariable logistic regression analysis, water quality metrics did not predict gastrointestinal illness among water recreators. Several variables other than water quality were associated acute gastrointestinal illness. The odds of such illness was increased by approximately two-fold by the presence of a chronic gastrointestinal condition, water exposure to the face, and by approximately 50% among those who fished (as opposed to other incidental contact activities). The odds of illness were reduced by approximately 50% among individuals who frequently used a water body for recreation. Unlike studies of swimmers at wastewater-impacted beaches that observed associations between water quality and illness incidence, this study did not. Public health protections for incidental contact recreation might focus on reducing exposure, particularly among fishers, those with chronic gastrointestinal conditions, and new recreators. Highlights: A cohort study of incidental contact water recreation was conducted. Measures of water quality were not predictive of gastrointestinal illness. Frequent use of a waterway decreases the risk of illness occurrence. Fishing may increase the risk of illness compared to other activities. Chronic gastrointestinal conditions increase the risk of illness.